1977
DOI: 10.1007/bf00199090
|View full text |Cite
|
Sign up to set email alerts
|

Direct cytotoxicity test applied to patients in stage I and II of malignant skin melanoma

Abstract: Using the direct eytotox~!city test described by Takasugi and Klein (1970), 59patients suffering from localized malignant skin melanoma (stages I and I I) were investigated for cell-mediated immunity. On an average, peripheral Iymphoeytes obtained preoperatively from 52patients showed a higher cytotoxicity against one of two established melanoma cell lines (RPMI 7931) as compared to lymphocytes from eontrol persons. No significant differences were found between lymphocytotoxicity of the patients and the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1977
1977
1983
1983

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…A high percentage of those patients with Stage I or Stage If melanoma who were serially monitored postoperatively and who demonstrated persistent anti-tumor cytotoxicity against established melanoma cell lines were found to relapse within 1 year [32]. In the same study, those patients who demonstrated a progressive decline in anti-tumor cytotoxicity following surgery remained disease-free.…”
Section: Serial Assessment Of Tumor-associated Immunity In Patients Wmentioning
confidence: 91%
“…A high percentage of those patients with Stage I or Stage If melanoma who were serially monitored postoperatively and who demonstrated persistent anti-tumor cytotoxicity against established melanoma cell lines were found to relapse within 1 year [32]. In the same study, those patients who demonstrated a progressive decline in anti-tumor cytotoxicity following surgery remained disease-free.…”
Section: Serial Assessment Of Tumor-associated Immunity In Patients Wmentioning
confidence: 91%
“…This reactivity was determined as previously reported [13] by means of the microcytotoxicity assay (MCA) [24] described in detail elsewhere [12]. An established melanoma line RPMI 7931 served as the target.…”
Section: Natural Cytotoxicity (Nc)mentioning
confidence: 99%
“…Sera for determinations of immune complex activity were stored at -80°C without additives. Lymphocytes were separated by a sodium metroziate-Ficoll gradient method as described elsewhere [12]. The average yield was 106 lymphocytes/ml blood.…”
Section: Sera and Lymphocyte Preparationsmentioning
confidence: 99%
“…This has been demonstrated by means of various in vitro methods such as microcytotoxicity test (6, 9, 28), colony inhibition (13), lymphocyte migration inhibition (2, S ) , leukocyte adherence inhibition (12), and blast transformation tests (16). In recent years, however, doubts have been raised concerning the specificity of some of these methods (7,14,15,17,19,27).…”
Section: 00s-0ooos) It Appears Frommentioning
confidence: 96%